Simulated stress testing on asian currencies. - Chan, Inn Leng. (2008)
Events like the recent Asian financial crisis had triggered an urgent need for the development of simple and reliable stress testing models that did not require extensive subjective judgment. Kupiec(1998) proposed such a model based on historical covariance and volatilities. This paper, with the main intention of developing a model that could possibly facilitate future research on stress testing of non-linear instruments, adapted the Monte-Carlo simulation methodology to Kupiec's model. In addition, both models were further adapted to account for fat tails in the returns distribution. All four models were tested on a portfolio of highly stressed Asian currencies for their reliability and robustness.